The Impact of Positive Agricultural Income Shocks on Rural Chinese Households - Leight, Jessica (Published by Oxford University Press on behalf of the World Bank, 2021)
In the post-collectivization period, rural Chinese households were required to sell part of their grain output to the state at a below-market price; however, increases in this quota price beginning in 1993 generated substantial positive income shocks. These income shocks also varied cross-sectionally in accordance with crop composition given that quotas were systematically larger for rice-producing households, generating a quasi-random source of variation in the size of the shock driven by climatic variation in suitability for rice cultivation. Households induced to experience relatively larger income shocks show evidence of decreased agricultural investment, increased investment in non-agricultural businesses, and increased migration as households gain increased income, consistent with the hypothesis that credit constraints may have constrained some households from entering non-agricultural production ex ante. In addition, there is evidence that these households were concentrated among households who had not previously diversified out of agriculture.